Infections with biological therapy: strategies for risk minimization in tropical and developing countries - Pérez-Díaz, Carlos E.; Uribe-Pardo, Erika; Calixto, Omar-Javier; Faccini-Martínez, Álvaro A.; Rodriguez-Morales, Alfonso J. (The Journal of Infection in Developing Countries, 2016)
In recent decades, biological therapy has enabled disease activity control and improved quality of life in patients with autoimmune diseases. These therapies that are involved in immune response modifications and change multiple immunological pathways induce an incremental risk for certain infectious diseases. Though there have been recent advances in risk assessment for biological therapy, there is a lack of data and recommendations for assessing risks in populations with high prevalence of infectious diseases, such as those located in tropical areas and developing countries. We performed a review on infections with biological therapy as well strategies for risk minimization in areas with a high prevalence of tropical diseases.